Vikkas ķeltu saknes - Saveļjeva, Olga (Latvijas Universitāte, 2009)
Bakalaura darbs „Vikkas Ķeltu Saknes” ir ieskats mītoloģijā un kultūrā. Šis darbs parāda aspektus, kuros seno ķeltu reliģija un modernā neo-pagāniskā kustība „Vikka” līdzinās un atšķiras. Lai parādītu līdzīgos un atšķirīgos aspektus, bakalaura darbā iekļauta informācija, kas skar katru tēmu atsevišķi. Tādējādi darba teorētiskajā daļā apskatīta seno ķeltu ikdienas dzīve un kultūra, kā arī Vikkas reliģijas pamati. Praktiskajā daļā veikta abu reliģiju salīdzinoša analīze. Atslēgvārdi ir: ķelti, vikka, vēsture, reliģija un mitoloģija.

The Bachelor thesis „Celtic Roots of Wicca” is an insight into a rather specific field of study: Mythology and Culture studies. This paper deals with the similarities between the Religion of the Ancient Celts and modern neo-Pagan movement called Wicca. In order to reveal the most characteristic similarities of these two religions, the Bachelor thesis includes a brief information on both themes before the beginning of the close analysis. It is done to give an insight into the life and culture of the Ancient Celts as well as the origin and the main concepts of the new pagan religion. This information is included in the theoretical part of this paper. Practical part, on its side, contains an analysis of both religions in a form of comparison and contrast. The key words for this paper are: celts, wicca, history, religion and mythology.
Celtic Roots Of Vicca
Keywords: Filoloģija